Introductory words (PUBMET, 2022)
Since 2014, the PUBMET international conference has served as a significant venue for gathering editors, publishers, librarians, journalists, policymakers, scholars and practitioners investigating and advancing scholarly communication in open science. The ninth PUBMET2022 conference was held at the University of Zadar from 14 to 16 September 2022, continuing a series of very successful conferences organised by the University of Zadar, Croatian Association for Scientific Communication - ZNAK, University of Zagreb, University of Rijeka and Ruđer Bošković Institute, under the auspices of the OPERAS consortium, OpenAIRE, the European Association of Science Editors (EASE) and SPARC Europe.We are happy that after two years of holding the conference online, we met again in person to discuss the latest developments in scientific communication and its most visible part, scientific publishing, and to share our knowledge, visions, expertise and the outcomes of numerous studies in this interdisciplinary field. This year we have seen the development and application of the principles of open science and open access as a prerequisite for achieving innovative scientific communication. Sharing all outputs in the earliest stages of research, including research data, software, protocols, methods, laboratory notes, reviewers’ reports, and publications, is the basis for the accelerated development of responsible science.This year’s PUBMET2022 has brought us a series of invited lectures, short presentations, panel discussions, posters, and workshops, discussing the progress of open science and promoting transparent and informed reporting on the results of scientific research. PUBMET2022 is the result of the year-long hard work of the programme and organising committees. Our excellent speakers, poster presenters, panellists, workshop leaders and moderators contributed to the conference’s success with their valuable, carefully selected and peer-reviewed content. In addition, more than 300 registered participants from 42 countries attended the conference in person or online, providing exciting questions and comments and sharing their opinions.Major themes of PUBMET2022 include:▸ Redesigning of open access - what can the scientific community do to retain rights over their research results, and what are the alternatives to the high fees for publishing in open access;▸ Raising efficiency and effectiveness in scholarly communication - changes that have been achieved by applying the principles of open science bring numerous advantages for scholars, but raise some new challenges;▸ The fairness of open science – transparency, responsibility, equity, diversity and cooperation in creating and sharing knowledge must be uncompromising;▸ Potentials of public engagement in science - how can research results make a more significant and positive impact on society?;▸ Assessing the quality of the research process, research outputs and publication channels - how does open science change the traditional quantitative research assessment criteria?